2014
DOI: 10.1126/science.1259694
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory formation of a scaled protostellar jet by coaligned poloidal magnetic field

Abstract: Although bipolar jets are seen emerging from a wide variety of astrophysical systems, the issue of their formation and morphology beyond their launching is still under study. Our scaled laboratory experiments, representative of young stellar object outflows, reveal that stable and narrow collimation of the entire flow can result from the presence of a poloidal magnetic field whose strength is consistent with observations. The laboratory plasma becomes focused with an interior cavity. This gives rise to a stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(129 citation statements)
references
References 31 publications
(45 reference statements)
6
120
0
1
Order By: Relevance
“…The dynamics of the laboratory-produced jets was shown to be scalable to YSOs jets [1,2] as both systems are to a first approximation well described by magnetohydrodynamics (MHD) [12,13]. The laboratory evidence for the poloidal collimation of jets thus offers an explanation of the observed long range collimation of young stellar jets [14].…”
Section: Recent Work and Astrophysical Implicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…The dynamics of the laboratory-produced jets was shown to be scalable to YSOs jets [1,2] as both systems are to a first approximation well described by magnetohydrodynamics (MHD) [12,13]. The laboratory evidence for the poloidal collimation of jets thus offers an explanation of the observed long range collimation of young stellar jets [14].…”
Section: Recent Work and Astrophysical Implicationsmentioning
confidence: 98%
“…Recent laboratory studies [1,2,3] and pertinent astrophysical simulations [4,5,6] have shown the viability of poloidal (i.e. axial) magnetic fields to directly result in the collimation of wide-angle outflows and the formation of jets in astrophysical accreting systems [7,8], such as young stellar objects (YSO).…”
Section: Recent Work and Astrophysical Implicationsmentioning
confidence: 99%
“…The other explanation is that dust is genuinely destroyed in a narrow annulus around the inner shell. Other more exotic causes not involving dust destruction could also be considered, such as magneto-hydrodynamic interactions between the wind and large-scale magnetic fields, as explored by van Marle et al (2014) and Albertazzi et al (2014).…”
Section: Possible Modelmentioning
confidence: 99%
“…In the aspect of astrophysics, a high magnetic field is related to many high-energy astrophenomena, such as the jet formation [5] , magnetic reconnection (MR) [6,7] and collisionless shock formations. Laboratory generation of strong magnetic fields makes it possible to study them in a new regime and controllable way.…”
Section: Magnetic-field Generation In the Laboratorymentioning
confidence: 99%